First report of Toumeyella parvicornis (Cockerell) in Europe (Hemiptera: Coccidae) - Garonna, Antonio P.; Scarpato, Salvatore; Vicinanza, Francesco; Espinosa, Bruno (Zootaxa, 2015)
Toumeyella parvicornis (Cockerell), the Pine tortoise scale, is reported for the first time from Europe. Pre-imaginal instars and adults were observed starting from the fall of 2014 in several municipalities of Campania (Italy). Since the species is recorded as a harmful pest of several pine species in North America and the Caribbean, the presence of this alien insect in Europe is alarming and represents a possible major threat for native pine species and related economic activities.